2014
DOI: 10.1352/1934-9556-52.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Physical Activity as Perceived by Older Adults With Intellectual Disability

Abstract: Older people with intellectual disability (ID) are characterized by low physical activity (PA) levels. PA is important for reducing health risks and maintaining adequate fitness levels for performing activities of daily living. The aim of this study was to explore preferences of older adults with ID for specific physical activities, and to gain insight into facilitators and barriers to engaging into PA. Fourteen in-depth interviews and four focus groups were undertaken, with a total of 40 older adults with mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 39 publications
5
59
0
1
Order By: Relevance
“…Sites that described more success with the programme provided facilitators that aided with implementation and felt positively about the programme materials. The facilitators discussed by these sites (i.e., making activity fun, providing choices and spending time with staff) were consistent with the literature (Bodde & Seo, ; Dixon‐Ibarra et al., ; Frey et al., ; Mahy et al., ; van Schijndel‐Speet et al., ). Similar to Humphries et al.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Sites that described more success with the programme provided facilitators that aided with implementation and felt positively about the programme materials. The facilitators discussed by these sites (i.e., making activity fun, providing choices and spending time with staff) were consistent with the literature (Bodde & Seo, ; Dixon‐Ibarra et al., ; Frey et al., ; Mahy et al., ; van Schijndel‐Speet et al., ). Similar to Humphries et al.…”
Section: Discussionsupporting
confidence: 77%
“…Sites that described more success with the programme provided facilitators that aided with implementation and felt positively about the programme materials. The facilitators discussed by these sites (i.e., making activity fun, providing choices and spending time with staff) were consistent with the literature (Bodde & Seo, 2009;Dixon-Ibarra et al, 2016;Frey et al, 2005;Mahy et al, 2010;van Schijndel-Speet et al, 2014). Similar to Humphries et al (2008) pilot intervention of Menu-Aidds nutritional programme for the group home setting, the current pilot had group home sites that were "too busy" to fully implement the programme and other sites that had positive attitudes towards implementation, perhaps indicating staff 's readiness to implement a health promotion programme varied.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…To motivate adults with ID to do exercise, it seems important to previously identify the type of activity that could generate greater acceptance and higher levels of adherence. In this respect, van Schijndel‐Speet, Evenhuis, van Wijck, van Empelen & Echteld () reported that both dance and activities with musical support were some of the favourite pastimes of older adults with ID. It has been observed that dancing constitutes a very positive stimulus that can help to increase the practice of physical activity in people with ID (Shih & Chiu ).…”
Section: Introductionmentioning
confidence: 99%
“…Esse resultado corrobora com outros estudos que mostram que as questões financeiras, falta de opções, a falta de apoio social e de apoio político e financeiro, instalações acessíveis, a proximidade da localização, boas oportunidades para a prática, pessoas especializadas, interferem e são preditores de baixo nível de AF para pessoas com DI [21][22] . Um estudo também mostrou que a questão mais crítica para o baixo nível de AF foi a falta de políticas claras.…”
Section: Discussionunclassified